A educação linguística e a formação inicial de professores de língua portuguesa: uma proposta para o letramento - Melo, Shirlei Barbieiro de (2009)
In present societies, to know how to read and write, how to use reading and writing skills in different daily situations are indispensable needs for any person to be able to practice his or her citizenship fully and for nations in general to develop in social, cultural and political levels. Notwithstanding, it is observed that there have been many difficulties for schools to effectively guarantee to individuals the learning of how to read and write. For this purpose, it is necessary to think of a way of teaching a maternal language in a more and more useful way and contextually meaningful, with focus on the Linguistic Education and the phenomenon of Literacy. In this sense, this dissertation approaches the question of the initial formation of teachers of the Portuguese Language with focus on the Linguistic Education and on the Literacy, based on the Case Study methodology research, focusing the analysis of educational practice of teachers of the 5th grade, fundamental teaching, level I. To reach the proposed objectives, we present the pedagogic and linguistic elementary aspects, from the theoretical point of view about the Linguistic Education and the Literacy phenomenon in relation to formation of Portuguese Language teachers. We have analyzed the educative practice of teachers in the teaching of the maternal language as well as the official documents of the Ministry of Education relating to the formation of such professionals. After analysis of the data, the results have shown that the practice of teachers (of the case study) is turned towards the teaching of a language centered on the written verbal language, on its structural rules and combinations, in a non-contextualized manner, disregarding the important roll of the language in the act of communication among students in social interactions. Thus, such professionals need a continuous practical and theoretical formation with focus on the Linguistic Education and on the Literacy in order to develop the teaching of the Portuguese Language centered on the social practices of reading and writing